The influence of prices and promotions on student decisions - Syaifuddin, Syaifuddin (Jurnal Mantik, 2024)
This research was conducted to determine the influence of price and promotion on students' decisions in choosing a private university, where the object of this research is STIE Yasa Anggana Garut. This research used a quantitative approach. The number of samples was determined using the Slovin formula, the sample obtained was 226 respondents. The data analysis used includes; validity test, simple correlation coefficient test, classical assumption test, multiple simple correlation coefficient test, coefficient of determination test, multiple linear regression analysis, Hypothesis Testing. Partial Test (t Test) and Model Feasibility Test (F Test). Simultaneously, the Price and Promotion variables have a significant influence on Student Decisions. This is proven by the calculated F value being greater than the F table value, namely 14.915 > 1.93. From the results of the multiple regression equation, it can be seen that Price and Promotion have a positive influence on Student Decisions, thus if Price and Promotion are increased then student Decisions will also increase. The coefficient of determination (R²) is 0.49, which shows that price and promotion are able to jointly explain 49% of STIE Yasa Anggana Garut students' decisions, while the remaining 51% is influenced by other variables that were not studied. Based on these results, efforts need to be made by STIE Yasa Anggana Garut to improve student decisions by fulfilling student satisfaction with the educational services provided while still prioritizing the quality of the lecture process